Adults of Sun Coral Tubastraea coccinea (Lesson 1829) Are Resistant to New Antifouling Biocides - Martins, Isabela [UNESP]; Capel, Kátia Cristina Cruz; Abessa, Denis Moledo de Souza [UNESP] (MDPI, 2024)
Biocides used in antifouling (AF) paints, such as 4,5-dichlorine-2-n-octyl-4-isothiazole-3-one (DCOIT), can gradually leach into the environment. Some AF compounds can persist in the marine environment and cause harmful effects to non-target organisms. Nanoengineered materials, such as mesoporous silica nanocapsules (SiNCs) containing AF compounds, have been developed to control their release rate and reduce their toxicity to aquatic organisms. This study aimed to evaluate the acute toxicity of new nanoengineered materials, SiNC-DCOIT and a silver-coated form (SiNC-DCOIT-Ag), as well as the free form of DCOIT and empty nanocapsules (SiNCs), on the sun coral Tubastraea coccinea. T. coccinea is an invasive species and can be an alternative test organism for evaluating the risks to native species, as most native corals are currently threatened. The colonies were collected from the Alcatrazes Archipelago, SP, Brazil, and acclimatized to laboratory conditions. They were exposed for 96 h to different concentrations of the tested substances: 3.33, 10, 33, and 100 µg L−1 of free DCOIT; 500, 1000, 2000, and 4000 µg L−1 of SiNC; and 74.1, 222.2, 666.7, and 2000 µg L−1 of SiNC-DCOIT and SiNC-DCOIT-Ag. The test chambers consisted of 500 mL flasks containing the test solutions, and the tests were maintained under constant aeration, a constant temperature of 23 ± 2 °C, and photoperiod of 12 h:12 h (light/dark). At the end of the experiments, no lethal effect was observed; however, some sublethal effects were noticeable, such as the exposure of the skeleton in most of the concentrations and replicates, except for the controls, and embrittlement at higher concentrations. Adults of T. coccinea were considered slightly sensitive to the tested substances. This resistance may indicate a greater capacity for proliferation in the species, which is favored in substrates containing antifouling paints, to the detriment of the native species.
Keywords: antifouling; DCOIT; ecotoxicology; nanomaterials; Tubastraea coccinea